PRE-SERVICE EFL TEACHERS’ CREATIVE THINKING - Lamhot Naibaho (Universitas Kuningan, 2022)
This study aims to investigate the pre-service teachers’ creative thinking at the faculty of Teacher Training and Education, Universitas Kristen Indonesia. It is limited to the difference of creative thinking between the male and female students. It was conducted at the Christian University of Indonesia within a period of 3 months from February to May 2021. The research design used was ex-post facto. The research subjects are 36 semester students who were selected purposively. The research instrument used is a standardized essay test. The data taken trough test were analyzed using descriptively, besides using a descriptive quantative, the data of the research were also analyzed using independent t test trough SPSS. The results of this study shows that the faculty of teacher training and education students’ creative thinking skills is at the level of “good” category, which is 63.69%. From a further analysis, it is found that the comparison between male and female students’ creative thinking skills did not have a significant difference. Thus, it can be concluded that male students creative thinking ability are much the same with the female students’ creative thinking ability at the Faculty of Teacher Training and Education, Universitas Kristen Indonesia.Keywords: creative thinking; teaching English; male and female.